PENGARUH DPK, CAR, NPL, ROA, JUMLAH SBI TERHADAP PENYALURAN KREDIT - Vina Roschiana, 09.05.52.0129; Suwarti, Titiek (Students Journal of Accounting and Banking, 2013)
Research background by the emergence of a variety of risks that occur in bank lending increasing especially in commercial banks registered in BEI. therefore necessary to test factors that influence the amount of bank credit which includes deposits, CAR, NPL, ROA and placement of funds in Bank Indonesia certificates (SBI). The method of analysis in this study uses regression multi independent .Variabel used in this study is deposits, CAR, NPL, ROA and placement of fundlys in Bank Indonesia certificates (SBI), the study sample was enrolled in banking bursa effect Indonesia (BEI) for the period 2008-2011.Data collected with the purposive sampling.Total there are 21 banking companies taken as a sample. This result of the study to show thatÂ DPK and ROA significant positive to credit of banking. SBI negatif significant, unfortunatelyÂ CAR no negative effect significant. While NPL positif and no significant. Keywords: DPK, CAR, NPL, ROA,sum of SBI and credit.